2017
DOI: 10.1101/135301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenome-wide association study of asthma and wheeze in childhood and adolescence

Abstract: Asthma heritability has only been partially explained by genetic variants and is known to be sensitive to environmental factors, implicating epigenetic modifications such as DNA methylation in its pathogenesis.Using data collected in the Avon Longitudinal Study of Parents and Children (ALSPAC), we assessed associations of asthma and wheeze with DNA methylation at 7.5 years and 16.5 years, at over 450,000 CpG sites in DNA from the peripheral blood of approx. 1000 participants. We used Mendelian randomization (M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…One of the limitations of our study is the fact that the time se- Findings from previous studies suggest that the associations observed between DNA methylation and asthma are largely driven by eosinophils 22,23 that are known to be involved in airway inflammation present in T-helper 2-type asthmatic phenotypes. 38 However, we used a quite robust method for cell composition adjustment and we believe that the differences observed in PM20D1 are not likely to be driven by eosinophil count.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…One of the limitations of our study is the fact that the time se- Findings from previous studies suggest that the associations observed between DNA methylation and asthma are largely driven by eosinophils 22,23 that are known to be involved in airway inflammation present in T-helper 2-type asthmatic phenotypes. 38 However, we used a quite robust method for cell composition adjustment and we believe that the differences observed in PM20D1 are not likely to be driven by eosinophil count.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, the magnitude of the associations for wheezing and asthma candidate CpGs identified in several previous EWAS was also small. 22,23,31 As the power of our exploratory EWAS was relatively low, we used a more powerful approach that allowed us to identify a wheezing-related differentially methylated region located in PM20D1 gene. This gene codes peptidase M20 domain-containing one enzyme that regulates production of N-fatty-acyl amino acids, which are a large family of more than 70 endogenous signalling molecules involved in pain and inflammation regulation, and their metabolites are important mediators of chronic airway inflammation in asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, also gender-specific methylation structures were found, as CpG hypermethylation of the receptor tyrosine kinase AXL in newborns blood was associated with wheeze at age 6 especially in girls [56]. Epigenome-wide association studies (EWAS) revealed consistently hypomethylated signatures driven by higher numbers of eosinophil, a granular cell type that is known to be centrally involved in allergic inflammatory processes [57]. Moreover, low methylation and subsequent overexpression of T-cell developmental genes including runt-related transcription factor 3 (RUNX3) and T-cell immunoreceptor with Ig and Immunoreceptor tyrosine-based inhibitory motif (ITIM) domains (TIGIT) have been demonstrated in asthmatics [58].…”
Section: Epigenetic Influencesmentioning
confidence: 99%